CONCEPTUAL AGGREGATION OF CRIMINAL OFFENCES SEPARATION FROM COLLISION OF THE CRIMINAL LAW NORMS - Persidskis, Ainārs (Administrative and Criminal Justice, 2017)
The topic of the paper is the conceptual aggregation of criminal offences separation from collision of the Criminal Law norms. The conceptual aggregation of criminal offences is the most difficult type of all multiplicity types of criminal offences. This research paper provides an overview of the conceptual aggregation of criminal offences separation from collision of the Criminal Law norms. In the paper is given analyses of conceptual aggregation of criminal offences separation from collision of the Criminal Law norms. At the end of research paper is given conclusion and the proposal to separate the conceptual aggregation of criminal offences from collision of the Criminal Law norms.